Scramble Learning Model to Improve the Ability Reading the Quran in Elementary School/Model Pembelajaran Scramble untuk Meningkatkan Kemampuan Membaca Al-Quran pada Mata Pelajaran Al-Quran Hadits di Madrasah Ibtidaiyah - Purniadi Putra; Syafrudin Syafrudin (STAI Ma'had Aly Al-Hikam Malang, 2020)
The purpose of this study is to contribute to the ability to read Al-Qur'an for MI children on the subject of the Al-Qur'an Hadith because reading the Al-Qur'an becomes the flagship program at MI Muhammadiyah Ketapang. This research method uses descriptive qualitative research on classroom action research (CAR). The results of this study are the Scramble Learning model in the Al-Qur'an-Hadith which has an influence in improving the competence in reading short surah choices after applying the Scramble model proven research results show that the level of competence in reciting and reading Al-Quran verses in subjects Al-Qur'an Hadith cycle I reached 91.3% enough category and cycle II there was an increase in achieving Al-Quran reading with Al-Qur'an Hadith students obtained 91.5% very good category.